CONSISTENCY OF DISTRIBUTED SYSTEM WITH ACTIVE INITIATOR PROCESS WITHOUT USELESS CHECKPOINTS - Gopalan, N. P.; Nagarajan, K. (International Journal of Computing, 2014)
Checkpointing mechanism is the one of the best attractive approach for providing software fault tolerance in distributed message passing systems. This paper aims to implement a distributed checkpointing technique, which eliminates the drawbacks of the centralized approach like “domino effect”, “useless checkpoint” (checkpoints that do not contribute to global consistency), and “hidden and zigzag” dependencies. The proposed checkpointing protocol has a checkpoint initiator, but, coordination among the local checkpoints is done in a distributed fashion. This guaranty that no message would be lost in case of failure occurs, has been maintained in this work by exchange of information among the processes. However, there is no central checkpoint initiator, but each of the processes takes turn to act as an initiator. Processes take local checkpoints only after being notified by the initiator. The processes synchronize their activities of the current checkpointing interval before finally committing their checkpoints. Thus, the checkpointing pattern described in this paper takes only those checkpoints that will contribute to the consistent global snapshot thereby eliminating the number of useless checkpoints.